Cryptography With Mceliece Algorithm (Code Based Cryptography) - Caleg Sadrak Sinaga; Alwi Findo Gultom; Dewi Ruth Nababan; Ari Rivaldo Simanjuntak; Edi Ginting (SEAN Institute, 2024)
Cryptography is the science used to protect information from unauthorized access. One promising cryptographic algorithm is the McEliece algorithm, which uses code-based cryptography. This algorithm was introduced by Robert McEliece in 1978 and is known for its resistance to attacks from quantum computers, which are expected to be able to break most current cryptographic algorithms. The McEliece algorithm uses binary Goppa code for encryption and decryption, offering high execution speed and resistance to various types of attacks. Although one of its main drawbacks is the large public key size, recent developments in research have shown progress in reducing the key size without sacrificing security. This study aims to explore the working mechanism of the McEliece algorithm, analyze its advantages and disadvantages, and discuss its potential applications in modern technology. The results of this study indicate that the McEliece algorithm has great potential in the field of quantum-safe cryptography, with applications ranging from secret communication to secure data storage.